The effect of activated carbon additives on lead sulphide thin film for solar cell applications - Nur Farha, Shaafi; Saifful Kamaluddin, Muzakir; Shujahadeen B., Aziz; Mohd Fakhrul Zamani, Kadir; Suresh, Thanakodi (Elsevier, 2021)
A photovoltaic device with an efficiency that could break the theoretical limit, exceeding ~60 is the focus in the research field in recent years. The efficiency of three important processes in a photovoltaic device need to be ensured to materialize the goal i.e., electron excitations, injections and regenerations. A multiple exciton generation (MEG) mechanism has been proven to increase the photovoltaic conversion efficiency - achievable via usage of small size lead chalcogenides as main light absorber of the photovoltaic device. An efficient electron injection in an excitonic solar cell could be achieved upon fulfilment of the following factors i.e., (i) LUMOfluorophore>CBphotoelectrode, and (ii) small offset between the LUMOfluorophore and CBphotoelectrode. The opto-electronic properties of lead chalcogenide are tuneable based on its size and morphology. Therefore, a synthesis method that could control the size and morphology of the yielded lead chalcogenide plays an important role. This research investigated the effect of additional activated carbon (AC) to the yielded PbS using vacuum thermal evaporator method. The PbS thin films were fabricated with addition of AC with different surface areas i.e., 80 m2/g, 650 m2/g and 1560 m2/g using thermal evaporator at vacuum pressure of 1.0 x 10-5 Torr. The surface area of the ACs was determined using Micromeritics ASAP 2020 BET (Brunauer-Emmett-Teller). The morphology, elemental analysis, crystal structure, opto-electronic, electron injection efficiency and electrical conductivity of the PbS thin film was characterized using Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive X-Ray Spectrometer (EDX), X-Ray Diffractometer (XRD), absorption spectrometer, photoluminescence spectrometer (PL), and Bridge Technology 4-point probes (4PP) respectively. The excited and ground states of the PbS, and redox potential of ionLic PMII electrolyte were determined using quantum chemical calculations at b3lyp/lanl2dz level of theory. Three important observations have been made i.e., (i) addition of AC with the PbS reactants affects the yielded morphology of PbS thin film, (ii) bare PbS/TiO2 device structure offers electron injection efficiency as high as 97% from the PbS to TiO2, and (iii) the bare PbS/TiO2 device structure would offer maximum VOC of ca. 1.7 V, however need to be paired with an electrolyte that possess oxidation potential of ca. -6.5 eV.